2007
DOI: 10.1021/ma062410z
|View full text |Cite
|
Sign up to set email alerts
|

New Photolabile Functional Polymers for Patterning onto Gold Obtained by Click Chemistry

Abstract: Nitroxide-mediated radical polymerization (NMRP) was used for the synthesis of the random copolymer poly[styrene-r-(4-propargyloxystyrene)] with a narrow molecular weight distribution (PDI ∼ 1.2). The material was postfunctionalized by polymer analogous reactions and via Cu(I)-catalyzed 1,3-dipolar cycloadditions (“click chemistry approach”) to provide a family of photopatternable functional polymers for nanotechnology applications. For this, a series of azides were designed in order to incorporate subunits wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…There are often unreacted pendent functional groups leftover. Because of its high reaction yield and mild reaction conditions, people have tried to introduce azides or acetylenes as novel pendent functionalities to the polymer backbone so that it can be used for further click modifications (76,77). One concern, however, is that this strategy will make sense only when the click functionalities are introduced by copolymerization, not polymer analogous reaction.…”
Section: Other Polymer-related Applications Of Click Chemistrymentioning
confidence: 99%
“…There are often unreacted pendent functional groups leftover. Because of its high reaction yield and mild reaction conditions, people have tried to introduce azides or acetylenes as novel pendent functionalities to the polymer backbone so that it can be used for further click modifications (76,77). One concern, however, is that this strategy will make sense only when the click functionalities are introduced by copolymerization, not polymer analogous reaction.…”
Section: Other Polymer-related Applications Of Click Chemistrymentioning
confidence: 99%
“…[26] Haddleton and coworkers [27] ''clicked'' azido functionalized, well-defined polymers onto organic resins and, very recently, Lee et al [28] modified nanobrushes by click chemistry. We could already demonstrate that alkyne containing random and block copolymers can be effectively modified in solution by such a 1,3-dipolar cycloaddition reaction to allow the introduction of photolabile and anchoring groups for their covalent attachment on various substrates [29] as well as pendant bulky adamantanyl units. [30] Furthermore, our approach resorting predominately to partly protected hydroxystyrene diblock copolymers synthesized by controlled radical polymerization (CRP) techniques has demonstrated that functionalized nanostructured surfaces can be successfully prepared.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of an azido-functionalized fluorescent dye (5) has been recently shown in our laboratories. [29] 4-Nitrobenzyl Azide, 4…”
Section: Introductionmentioning
confidence: 99%
“…Recently the application of nitroxidemediated free radical polymerization of AS has been used to prepare poly(hydroxystyrene/styrene) copolymers that were post functionalized by a similar approach. [16] Here we present the preparation of statistic copolymers of styrene and tBS for the preparation of polymers with variable loadings of functional groups through click chemistry.…”
Section: Introductionmentioning
confidence: 99%